Micropropagation Of Common Fig (Ficus Carica L.) Cv. Violette De Solliès - Ling, Wan Ting (2020)
The current study aims to establish a micropropagation protocol for the common fig (F. carica L.) cv. ‘Violette de Solliès’ to mass propagate true-to-type fig plantlets via apical bud culture. Young apical buds were surface sterilized using different concentrations and duration of disinfectants and cultured on MS medium supplemented with 4 mg/L BAP for the establishment of in vitro cultures